The Civil Review Proceeding in Cuba: Clearing the Darkness Around its Processing and Thee Grounds - Galbán Rodríguez, Liuba; Pipa Núñez, Raúl Alejandro (DIXI, 2016)
Purpose: to offr some reflctions about the need for perfecting the conception and processing of civil review in Cuba, especially in terms of regulation of three grounds that, in turn, are of criminal-functional dependency due to the diffilties of judicial practice at the time of achieving its admission, processing and solution. Description: criteria of procedural doctrine on the legal construction of review are provided regarding whether it is a remedy, a procedure or a true proceeding, which demonstrates a lack of unanimity that has transcended the global legislative order.Point of view: a comparative analysis of review at the Cuban procedural levels regarding judgments against which it proceeds; this shows a lack of uniform criteria by the judicial practice of the maximum forum.Conclusions: concrete proposals for amending the law are made for perfecting it, thus contributing to a better exercise of legal praxis. Th review is a proceeding that undoubtedly relates to the previous proceeding from which the resolution subject thereto comes from, aimed at safeguarding rights and serving as ultima ratio of realization of justice as a value and purpose of Law.
Keywords: civil review; grounds; order; judgement; judicial practice; justice